Betoging op Hemelvaartsdag. Midden, met zwarte jas: Drees, rechts naast hem: Vermeer, daarnaast: Mansholt, daarachter: Vos
Betoging op Hemelvaartsdag. Midden, met zwarte jas: Drees, rechts naast hem: Vermeer, daarnaast: Mansholt, daarachter: Vos.